Pelatihan Penggunaan Teknologi Untuk Pengelolaan Laporan Keuangan Di Sektor Usaha Kecil Dan Menengah Karanganyar - Lestari, Dewi Amelia; Restama, Arie; Huda, Ersyafaat; Subarkah, Johny (Bengawan : Jurnal Pengabdian Masyarakat, 2024)
Small and medium enterprises (SMEs) in Karanganyar Regency still face various obstacles in financial report management, such as limited knowledge of accounting and minimal utilization of digital technology. This has resulted in a lack of accuracy and transparency in transaction recording, as well as difficulties in accessing financing opportunities. This service program aims to enhance the capacity of SMEs to use simple technology to prepare more orderly and informative financial reports. The methods used in this activity are workshops, direct mentoring, and evaluation of training results. The activity was conducted over the course of one day, involving 25 SMEs in the Karanganyar Regency area. The findings in this community service indicate that the SME participants experienced a significant improvement in their understanding of basic accounting concepts and were able to operate digital technology to record and prepare basic financial reports, such as simple financial statements. The conclusion of this service is that technology-based training can have a positive impact on improving the financial managerial skills of SMEs. The sustainability of the next program to reach more entrepreneurs and strengthen the digital-based SME ecosystem.